THE EFFECT OF READING TEACHING MATERIAL FOR DIFFERENT LEARNING STYLES IN IMPROVING STUDENTS’ READING COMPREHENSION - Zul Astri; Isnaeni Wahab (Jurnal Bahasa Lingua Scientia, 2018)
This study aims to explain the relationship between student learning styles and student achievement in English Reading Comprehension and to determine how extents the teaching material meets the needs of students with different learning styles. Researchers conducted the One-Group Pretest-Posttest design where only one experimental group was given a pre-test and post-test. Data collection is done in several ways, namely by giving a questionnaire from Barsch Learning style inventory (1980), interviewing and conducting pre and post tests to determine the development of students' abilities before and after the presentation of the material. In addition, classroom observation was conducted to find out the classroom activities and students’ participation toward teaching material given. The data  revealed that the average of students’ result in pre-test was 38.92 % while the result of the average of students’ result in post-test was 68.58 %.  It may say that the students’ improvement in reading comprehension using the teaching material has a significant improvement. 100% of visual learners have improved the ability in English reading comprehension after being given the material. 100% of auditory learners also have an increase in the ability in English reading comprehension after the provision of teaching materials. Likewise with visual-auditory learners in which 100 percent of respondents experienced an increase. However, only 80 percent of 100 percent kinesthetic learners experience an increase after the provision of teaching materials. There are many factors that influence the students. It can be in the form of internal factors that trigger students' motivation in learning English.